Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1469540519893102
|View full text |Cite
|
Sign up to set email alerts
|

The role of nostalgia in retro sewing

Abstract: This article explores the role of nostalgia as a motivation for retro sewing and the ways in which nostalgia shapes the practices of retro sewing. Retro sewers circumvent typical models of clothing consumption by opting out of the commercial fashion cycle, and instead creating clothing for everyday use that replicates or is inspired by styles from the past. As such, the practice of retro sewing is inextricably linked to one or more of the many forms of nostalgia. Previous studies on consumers and nostalgia hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…A desire to maintain the 'naturalness' of food from traditional practices was paramount, reflecting a yearning for a bygone era (Pickering and Keightley, 2006). The idea of food-expressing identity is linked to a re-appropriation of the past in food culture (Armstead and McKinney, 2022). Pickering and Keightley (2006) discussed that such reinvention of historical goods is based on renewal of those goods to deal with the uncertainties of what the future holds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A desire to maintain the 'naturalness' of food from traditional practices was paramount, reflecting a yearning for a bygone era (Pickering and Keightley, 2006). The idea of food-expressing identity is linked to a re-appropriation of the past in food culture (Armstead and McKinney, 2022). Pickering and Keightley (2006) discussed that such reinvention of historical goods is based on renewal of those goods to deal with the uncertainties of what the future holds.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that ideals of processes and products in past times may have a contrasted element as representing a continuity to the identity of an individual (Armstead and McKinney, 2022). In this way, nostalgia becomes an idea of reconfiguring important elements of the past to suit modern and future ideals (Grainge, 2000).…”
Section: Social Identity Ethical Markers In Rural and Urban Australiamentioning
confidence: 99%